Antagonism between steady light and phosphodiesterase inhibitors on the kinetics of rod photoresponses. - Capovilla, M (1982)
Treatment of toad rods with phosphodiesterase inhibitors (3-isobutyl-1-methylxanthine, caffeine, theophylline, papaverine, and RO 20-1724) modifies the properties of the intracellular voltage responses to dim flashes of light. 3-Isobutyl-1-methylxanthine at 1-20 microM causes an increase in flash sensitivity and a slowing down of the kinetics of the photoresponses. When the drug concentration is greater than 20 microM, rods also show supralinear behavior, whereby doubling the intensity of a dim flash may increase the response by greater than 2-fold. Sensitivity, kinetics, and supralinear behavior can be restored to normal by steady background illumination while still in the presence of 3-isobutyl-1-methylxanthine. However, the intensity of the steady light needed to restore the sensitivity to control levels is not sufficient to accelerate the kinetics back to control values. The antagonism between the effects of 3-isobutyl-1-methylxanthine and the effects of background illumination is explained by assuming that: (i) the length of time to peak voltage responses to dim flashes of light is inversely proportional to the rate of a chemical reaction; (ii) the rate of this reaction is controlled by an enzyme that is inhibited competitively by 3-isobutyl-1-methylxanthine with a Ki of 3 x 10(-6) M; and (iii) the concentration of a cofactor of this reaction increases proportionally with the intensity of the background illumination.